Miliary Bovine Tuberculosis in Buffaloes in Al-Muthanna Governorate, Iraq - Al Salihi, Karima Akool; AL-Zuhairi, Ahmed Hanash; Jalil, Waleed Ibrahim (Journal of Buffalo Science, 2022)
Background: Bubalus bubalis (river buffaloes) are widely distributed in the southern marshes of Iraq. This study intends to record a case of miliary tuberculosis in buffalo for the first time in Al Muthanna abattoir, Iraq, with its clinical, gross, and histopathological findings and microbiological investigations. Case Description: Ten years old buffalo showed chronic cough, infertility, emaciation, debilitation, lower milk production, loss of weight, and loss of appetite for 2 months; during meat inspection, thousands of various size typical tubercles, yellowish, granulomatous, and caseous lesions were distributed over all the body. Results: Microscopically, features of tuberculosis granuloma lesions were observed and revealed oval or round caseous necrosis with irregular central areas. Moreover, mineralization was enclosed by a thin to a broad layer of diverse inflammatory cells and solid collagenous connective tissue sheath. Moreover, a direct smear from the lesion stained by the Ziehl-Neelsen stain showed a slightly curved, red, and straight rod that was seen alone or in clusters, indicating the bacilli of tuberculosis. Additionally, the growing bacteria on the Löwenstein-Jensen media slant revealed flat, smooth, moist, white, not pigmented colonies suggestive of M. Bovis that revealed typical results with traditional biochemical tests, including negative reaction to nitrate reduction, niacin test, and deamination of pyrazinamide. Conclusion: For the author’s knowledge, this is the first case report of miliary bovine tuberculosis in buffalo in Iraq. The diagnosis was made according to clinical signs, gross pathology, and histopathological features supported by Ziehl-Neelsen stain and bacterial isolation. The author recommends future epidemiological molecular studies to improve the diagnosis tools of bovine tuberculosis in Iraq and investigate the causative agent M. Bovis to establish the roles for disease control that becomes much more challenging.